Measures to overcome the barriers that hinder the adoption of energy-efficient technologies in the Brazilian building segment - Cristino, Talita Mariane [UNESP] (2024)
The imminent global energy crisis combined with an uncertain climate future highlights the urgency to mitigate undesirable concerns about excessive energy consumption and its environmental impacts. This scenario has led to the development of several actions to reduce global energy consumption. For decades, these actions were directed towards to the industrial segment, since it was the greatest energy consumer in society. However, as time went by, residential, commercial, and public buildings have gained prominence, since they have become responsible for one-third of global final energy consumed and for 15% of greenhouse gas emissions. This scenario is not quite different in Brazil. The energy consumption of this segment has also been growing consistently over the last decades. Therefore, it is important to find ways to reduce the energy consumption of this segment without affecting the comfort and well-being of society. Energy efficiency is the key to solving this issue, in other words, the adoption of energy-efficient (EE) technologies is the best way to deal with this challenge. However, despite the benefits and positive projections linked to such technologies, they have not been widely adopted in buildings, due to the existence of barriers that hinder their adoption. In the literature, there are many publications aimed to identify such barriers. But, just a small portion of them focus on measures to overcome them. And none is dedicated to the Brazilian reality. Therefore, this research aimed to fill this gap. Firstly, it was important to develop a conceptual framework that provides a comprehensive understanding of the barriers that hinder the adoption of EE technologies. Thus, as a result, this framework enabled the delineation of the process of EE technology adoption, highlighting its necessary steps and the stakeholders involved. Notably, the adoption process was subdivided into four stages (Motivation, Information, Planning/Execution, and Results) shaped by both the government and the market. This result still allowed for a meticulous mapping of the barriers specific to the Brazilian context within the adoption process, thus identifying the process stages at which each barrier may emerge. Subsequently, it was possible to study the interrelationships between the barriers that emerge at each stage of the adoption process. This analysis was performed using the ISM (Interpretative Structural Modelling) technique. As a result, it was possible to construct hierarchical structures among the barriers that emerge in each stage of the adoption process, enabling the identification of the critical ones: lack of knowledge on energy efficiency by regulators and legislators (Government Support); lack of financial incentives (“Motivation” phase); lack of demonstration projects (“Information” phase); lack of technical competence and lack of adequate technologies (“Planning/Execution” phase); and lack of good marketing strategies (Market Expansion). From the identification of these critical barriers, it was possible to propose measures to overcome them. Initially, a literature review was conducted to identify such measures. Subsequently, these measures were proposed specifically for the Brazilian context. And although this research had suggested measures to overcome the critical barriers, it was also important to present additional suggestions to overcome the remaining barriers that hinder the adoption of EE technologies in the Brazilian building segment. This strategy ensures that not only the critical barriers are addressed, but also the less prominent ones, thereby facilitating a more effective transition to energy-efficient practices across the entire segment. By proposing measures to overcome barriers to the adoption of EE technologies in the building segment, this research contributes significantly to enhancing the efficiency and sustainability of Brazilian buildings. Additionally, it stimulates economic growth and enhances the country’s competitiveness regarding energy issues in the building segment. Thus, the suggested measures not only address immediate challenges but also pave the way for long-term benefits and progress in the Brazilian building segment.